Meta-Analysis of Down Syndrome Cortical Development Reveals Underdeveloped State of the Science - Risgaard, Kirstin A.; Sorci, Isabella A.; Mohan, Sruti; Bhattacharyya, Anita (Frontiers in Cellular Neuroscience, 2022)
Neurodevelopmental impairment contributes to the hallmark cognitive disability in individuals with Down syndrome (DS, trisomy 21, T21). The appearance of cognitive deficits in infancy suggests that alterations emerge during the earliest stages of neural development and continue throughout the lifespan in DS. Neural correlates of intellectual and language function include cortical structures, specifically temporal and frontal lobes that are smaller in DS. Yet, despite increased understanding of the DS cognitive-behavioral phenotype in childhood, there is very little structural and histological information to help explain the deficits. Consequently, attempts to effectively design therapeutic targets or interventions are limited. We present a systematic review of published research on cortical development in DS that reveals a paucity of studies that rigorously identify cellular features that may underlie the gross morphological deficits of the developing DS brain. We assessed 115 published reports retrieved through PubMed and other sources and found that only 23 reported histological and/or immunohistochemical data to define cell composition affected in DS post-mortem brain. Further, our analysis reveals that many reports have limited samples sizes and few DS samples, making it difficult to draw conclusions that are generally applicable to the DS population. Thus, the lack of replication and limited number of studies indicate that more developmentally focused research, ideally using equal numbers of age-matched samples in analyses, is needed to elucidate the cellular nature of smaller brain size in DS.